2018
DOI: 10.4162/nrp.2018.12.4.298
|View full text |Cite
|
Sign up to set email alerts
|

The effects ofBrassica junceaL. leaf extract on obesity and lipid profiles of rats fed a high-fat/high-cholesterol diet

Abstract: BACKGROUND/OBJECTIVESObesity is a global health problem of significant importance which increases mortality. In place of anti-obesity drugs, natural products are being developed as alternative therapeutic materials. In this study, we investigated the effect of Brassica juncea L. leaf extract (BLE) on fat deposition and lipid profiles in high-fat, high-cholesterol diet (HFC)-induced obese rats.MATERIALS/METHODSMale Sprague-Dawley rats were divided into four groups (n = 8 per group) according to diet: normal die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
2
13
0
1
Order By: Relevance
“…These results are in accordance with the literature published on other Brassicaceae vegetables; indeed, many preclinical and clinical reports demonstrated their antioxidant activity (Bahadoran et al, 2011), anti-obesity and hypo-lipidemic effects in rats fed with HF diet (Lee, Kim, & Lee, 2018). For instance, 4-week supplementation with Brassica rapa L. (var.…”
Section: Effects Of Eruca Sativa Mill Seed Extract On the Watsupporting
confidence: 91%
“…These results are in accordance with the literature published on other Brassicaceae vegetables; indeed, many preclinical and clinical reports demonstrated their antioxidant activity (Bahadoran et al, 2011), anti-obesity and hypo-lipidemic effects in rats fed with HF diet (Lee, Kim, & Lee, 2018). For instance, 4-week supplementation with Brassica rapa L. (var.…”
Section: Effects Of Eruca Sativa Mill Seed Extract On the Watsupporting
confidence: 91%
“…These observations are supported by another study in Korea. They suggested that hepatic fat accumulation may be a possible cause for liver dysfunction which in turn elevates the levels of these hepatic markers (Lee et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the liver and lipid levels improved after extract treatment, so Brassica juncea L. leaf 80% (v/v) ethanol extract may have a therapeutic effect on obesity, which seems to be related to the inhibition of G6pdh, Acc, and Fas gene expression. (J.J. Lee et al, 2018).…”
Section: Anti-obesitymentioning
confidence: 99%